A Study of Ion Cluster Theory of Molten Silicates and some Inorganic Substances : Handbook. - Guochang, Jiang (Materials Science Foundations (monograph series), 2009)
The first part of this monograph consists of a discussion of the microstructures of molten silicates and other inorganic substances. It is made up of seven chapters. Chapter 1 considers developments in ion-cluster theory. Chapter 2 introduces experimental approaches to the direct monitoring of a molten sample, such as hightemperature Raman spectroscopes which have successfully recorded Raman spectra from melts at temperatures of 2000K or more. Chapter 3 shows that five types of Si-O tetrahedron are appropriate microstructural units for setting up structural models. Chapter 4 confirms the SiOT.